Exploring The Contributions Of 5-Star Hotels In Bali Indonesia, To Social Development Pillars Of The SDGs: A Descriptive Qualitative Analysis - Yulita Suryantari; Hubertina Karolina Ngarbingan; Efraim Bavo Priyana (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The Sustainable Development Goals (SDGs) are a global development agenda designed to address economic, social, environmental, legal, and governance challenges. Tourism, including the hospitality industry, is a key sector highlighted within the SDGs framework. This study aims to examine the role of five-star hotels in Bali in advancing the SDGs, particularly focusing on the social development pillar. Using a descriptive qualitative method, the findings reveal that both five-star hotels in this study have implemented several relevant indicators of the SDGs' social pillar. Hotel A supports SDG 1 (No Poverty) through local employment and social security programs; SDG 2 (Zero Hunger) by distributing food packages to employees and their families; SDG 3 (Good Health and Well-being) through employee welfare programs; SDG 4 (Quality Education) via career development; and SDG 5 (Gender Equality) by promoting women in management roles. Meanwhile, Hotel B emphasizes SDG 1 through Corporate Social Responsibility (CSR) initiatives, SDG 3 by providing health insurance, SDG 4 through staff training, and SDG 5 by fostering an inclusive work environment. These findings demonstrate that the hospitality sector can contribute significantly to the SDGs in Indonesia, particularly in Bali as a major tourist destination. The measures taken by these hotels can serve as a model for sustainable social development practices within the hospitality industry.